Shape grammars for creative decisions: In the architectural project - Tching, J.; Reis, J.; Paio, A. (2013 8th Iberian Conference on Information Systems and Technologies (CISTI), 2013)
Shape grammars, used in applications in the field of Computational Creativity (CC), might provide the artists with applications to assist them in the creative process, not only creating solutions but also as a way of creating new ideas. In architecture, shape grammars can work with rules which will convey legal restrictions, space needs and goals that the architect needs or wants to fulfil, creating possible solutions to a project. A wide range of solutions can be tested in computational application based in shape grammars. These applications can also encourage the architect to go further in his creativity through the shape emergence where the conditions are fulfilled and presented as innovative and/or unexpected. Due to the strict rules they have to obey and to the issues they are supposed to respond and, not being a mere artistic intention but rather a response to a specific need/objective intention (space building), architectural projects show a set of common phases which might take a lot of advantages from computational applications and at the same time respond not only to the technical needs but also to the creative goals.